KINERJA GURU PAI DALAM PEMBELAJARAN PADA MASA PANDEMI DI SMK 1 NEGERI KECAMATAN LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Vivi Zanni; Arifmiboy; Salmi Wati; Iswantir (KOLONI, 2022)
This research was motivated by events that occurred in the field that researchers saw in SMK 1 Negeri Lembah Melintang while studying PAI. The author found difficulties in the performance of PAI teachers in planning, implementing, evaluating. PAI teacher performance during this pandemic in carrying out the main task of teaching (teaching), namely: the learning process during this pandemic the teacher experienced a process of difficulty in carrying out learning such as but there was no limited time then the system number of sessions was also limited, so usually the teacher explained the learning material or in that learning in one session it is full so that there is no repetition of the learning material that has been discussed earlier and the problem is this week's group 1 and tomorrow's group 2 so that the teacher repeats the material and that time is increasing in time where one learning material can so 4 or 5 meetings, so that the material is not achieved in accordance with the lesson plan. This study uses a qualitative descriptive method, which describes the events that occur in the field as they are. Data were analyzed by data collection techniques, and data analysis techniques. The results of this study are about the performance of PAI teachers in the aspect of learning planning during the pandemic. Is an activity related to efforts to formulate a program which includes everything that will be carried out, determination of goals, policies, directions to be taken, procedures and methods to be followed in an effort to achieve goals. And PAI teacher performance in the aspect of implementing learning during the pandemic. Learning implementation is the implementation of the learning implementation plan (RPP) that has been prepared by the teacher. The implementation of classroom learning activities is the core of the implementation of education which is marked by the existence of learning activities, as well as the performance of PAI teachers in the aspect of evaluating learning during a pandemic. Activities or methods shown to determine whether or not the learning objectives have been achieved and the learning process that has been carried out. At this stage a teacher is required to have the ability to approach and evaluate methods. Keyword: PAI Teacher Performance in Learning During the Pandemic Period.